The Pentapeptide RM-131 Promotes Food Intake and Adiposity in Wildtype Mice but Not in Mice Lacking the Ghrelin Receptor - Fischer, Katrin; Finan, Brian; Clemmensen, Christoffer; van der Ploeg, Lex H. T.; Tschöp, Matthias H.; Müller, Timo D. (Frontiers in Nutrition, 2015)
The gastrointestinal peptide hormone ghrelin is the endogenous ligand of the growth hormone secretagogue receptor (GHSR, a.k.a. ghrelin receptor, GHR). Currently, ghrelin is the only circulating peripheral hormone with the ability to promote a positive energy balance by stimulating food intake while decreasing energy expenditure and body fat utilization, as defined in rodents. Based on these and additional, beneficial effects on metabolism, the endogenous ghrelin system is considered an attractive target to treat diverse pathological conditions including those associated with eating/wasting disorders and cachexia. As the pharmacological potential of ghrelin is hampered by its relatively short half-life, ghrelin analogs with enhanced pharmacokinetics offer the potential to sustainably improve metabolism. One of these ghrelin analogs is the pentapeptide RM-131, which promotes food intake and adiposity with higher potency as compared to native ghrelin in rodents. Whereas the effect of RM-131 on energy metabolism is solidly confirmed in rodents, it remains elusive whether RM-131 exerts its effect solely via the ghrelin receptor. Accordingly, we assessed the receptor specificity of RM-131 to promote food intake and adiposity in mice lacking the GHR. Our data show that in wildtype mice RM-131 potently promotes weight gain and adiposity through stimulation of food intake. However, RM-131 fails to affect food intake and body weight in mice lacking the GHR, underlining that the anabolic effects of RM-131 are mediated via the ghrelin receptor in mice.